THE EFFECT OF PRODUCT INNOVATION, WORD OF MOUTH AND DIGITAL MARKETING ON CONSUMER BUYING INTEREST IN USED TIRE RUBBER CRAFTS IN PON VILLAGE - Syafrizal, Rodi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to examine the effect ofThe Influence of Product Innovation, Word Of Mouth and Digital Marketing on Consumer Buying Interest in Used Tire Rubber Crafts in Pon Village, the results of this study indicate that . 1)product innovation(X1) has no positive and significant effect on consumer buying interest (Y). 2) word of mouth (X2) has a positive and significant effect on consumer buying interest (Y). 3) digital marketing (X3) has a positive and significant effect on consumer buying interest (Y). 4) Simultaneously variable product innovation (X1 ), word of mouth (X2) and digital marketing (X3) have a positive effect on consumer buying interest (Y).